Thermal management system for electronic devices - И. В. Цевух; B. B. Спивак; А. И. Малюта; Т. Н. Шуба (Tekhnologiya i Konstruirovanie v Elektronnoi Apparature)
A four-channel thermal management system with low level of electromagnetic interference is proposed. The system is designed for single- and multi-core CPUs, GPUs, motherboard chipsets etc., emitting a heat flow with the density up to 200 W/cm2.